Russian Formalism Theory: Foundations and Principles-Applied to The "The Mother" Poem –Of Zharo Al-Duhoki - Tahir, Nizar S. (Humanities Journal of University of Zakho, 2017)
This study aims to identify the critical foundations and principles of the Russian formalism Theory and appllied these foundations on the poetic text in Kurdish literature. Russian formalism is considered one of the critical aesthetic and modern theories, which has a major impact on the progress of the global literary criticism. In this study that is so-called (Russian formalism Theory: foundations and principles-applied to the "The Mother " poem –of Zharo Al-Duhoki). After the presentation of the theoritical background on Russian formalism theory, we have extracted set of procedures and steps which through applying Russian formalism theory on the text. We have analysed this poem according to that theory and it appears that, the external and internal shapes of the poem are an effective method to analyze the hidden (codes) meanings within the text of the poem.